In vitro chemo-preventive activities of hydroxytyrosol: the main phenolic compound present in extra-virgin olive oil. Issue 1 (15th October 2015) - Rosignoli, Patrizia; Fuccelli, Raffaela; Sepporta, Maria Vittoria; Fabiani, Roberto
Abstract : The co-incubation in the culture medium with hydroxytyrosol [3, 4-dihydroxyphenyl ethanol (3, 4-DHPEA)], the main phenolic compound present in extra-virgin olive oil, and H2 O2 reduces the oxidative DNA damage in peripheral blood mononuclear cells (PBMC). Abstract : The co-incubation in the culture medium with hydroxytyrosol [3, 4-dihydroxyphenyl ethanol (3, 4-DHPEA)], the main phenolic compound present in extra-virgin olive oil, and H2 O2 reduces the oxidative DNA damage in peripheral blood mononuclear cells (PBMC). In this study we investigate, by the comet assay, the ability of 3, 4-DHPEA to inhibit the H2 O2 induced DNA damage when pre-incubated with PBMC and then removed before the exposure of cells to H2 O2 . Low doses of 3, 4-DHPEA (10–100 μM) pre-incubated for 30 min with PBMC reduced the DNA damage induced by the treatment with H2 O2 200 μM for 5 min at 4 °C. Prolonging the exposure time up to 6 h completely prevented the DNA damage. Furthermore we extensively analysed, by the MTT assay, the anti-proliferative activities of 3, 4-DHPEA on breast (MDA and MCF-7), prostate (LNCap and PC3) and colon (SW480 and HCT116) cancer cell lines and correlated these effects with the H2 O2 accumulation. The concentration of H2 O2 in the culture medium was measured by the ferrous ion oxidation–xylenol orange method. The proliferation of all the cell lines was inhibited but at different levels: the prostate cancer cells were more resistant to the growth inhibition with respect to breast and colon cancer cells. The ability of the different cell lines to remove H2 O2 from the culture medium was inversely correlated with their sensitivity to the anti-proliferative effect of 3, 4-DHPEA. Therefore, 3, 4-DHPEA may act as a chemopreventive agent acting on both initiation and promotion/progression phases of carcinogenesis.